Age effect on inter-pulse interval selection for ECAP measurement - Wu, Han; Yang, Xue-ying; Liang, Chao-qun; Yang, Jian-ming (Frontiers in Neuroscience, 2025)
IntroductionAge and duration of deafness significantly affect the auditory nerve (AN) health of cochlear implant (CI) users. In this study, we examine how age and duration of deafness impact Electrically Evoked Compound Action Potential (ECAP) amplitudes when the Inter-Pulse Interval (IPI) parameter in ECAP measurements is varied.MethodsOur participants were thirty-one Mandarin-speaking CI users with Nurotron/CS-20A (19 males and 12 females, 33 ears, aged 6–66 yrs). We investigated eleven distinct IPI settings, ranging from 290 μs to 590 μs (IPI = 290, 330, 350, 390, 410, 450, 470, 510, 530, 570, 590 μs).ResultsThe first result of our study was to find the optimal IPI of the participants. Furthermore, the optimal IPI was positively correlated with both the age of the participants (r = 0.6018, p = 0.0002) and the duration of deafness (r = 0.3479, p = 0.0473).DiscussionOur study sheds light on the pivotal role of age and duration of deafness in ECAP amplitudes and optimizing IPI settings. We recommend that CI users with advanced age and long duration of deafness use longer IPI parameters for ECAP measurements to obtain a more accurate ECAP waveform. These insights hold significant implications for tailoring CI programming and rehabilitation strategies to cater to the distinct needs of individuals across different ages and duration of deafness groups, ultimately enhancing the auditory experiences and outcomes of CI users.